Designing indicators for evaluation of Nursing education:A qualitative study - Khodaveisi, masood; Pazargadi, mehrnoosh; Yaghmaei, farideh; Alavi Majd, hamid (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Nursing education as a part of higher education has been expanding very rapidly in recent decades in the world. This situation caused to increase concern about quality of nursing education. This study aimed to identify indicators of evaluation in nursing education. Materials and methods: This research is a qualitative study, with content analysis approach which was done in three stages. In the first stage, semi-structured interview was done with 21 members of Nursing board, Deans, Deputies and evaluation committee's members in Nursing and Midwifery schools of type No.1 in Iran. Texts of interviews were analyzed through content analysis method and their understanding of evaluation of nursing education was determined. In the second stage, seven forms in the field of evaluation in nursing education at nursing schools and ministry of health have been collected and were studied by using content analysis method. In the third stage, by using comparative study and searched in databases of international nursing associations and scientific in the field of evaluation of nursing education, 11 forms available on the evaluation and accreditation in nursing education were identified and then, by using content analysis methods were studied. Domains and indicators of evaluation were extracted. Results: In the first phase, 16 themes related to evaluation’s challenges and 21 themes related to requirements in effective evaluation in nursing education were identified. In second phase, evaluation’s domains and indicators in documents and evaluation forms in Iran were identified and extracted. In third phase, evaluation’s domains and indicators in documents and evaluation forms at the level of international scientific associations and education were identified and extracted. Domains and indicators in the second stage were chosen as the base framework and then third stage findings were gradually added to it. Finally, after considering the challenges and requirements of evaluation, findings of research in three areas including of input, process and output, 9 domains and 141 indicators were classified and developed. Conclusion: Dynamic educational system requires the dynamic method evaluation. As in this study the indicators of evaluation were revised, these indicators can be used in internal evaluation, external evaluation, ranking and accreditation of nursing schools and nursing educational systems. Keywords: Evaluation Indexes; Nursing Education; Qualitative nursing research